2018
DOI: 10.1093/infdis/jiy057
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Breastfeeding to False-Positive Saliva Polymerase Chain Reaction for Newborn Congenital Cytomegalovirus Screening

Abstract: Real-time polymerase chain reaction (PCR) of saliva is highly sensitive for newborn congenital cytomegalovirus (CMV) screening. This study uses nationally published CMV seroprevalence and breastfeeding rates to estimate the contribution of CMV DNA in breast milk to false-positive saliva PCR results. The false-positive rates adjusted for breastfeeding ranged from 0.03% in white Hispanic persons to 0.14% in white non-Hispanic persons. Saliva CMV PCR for newborn screening is highly sensitive, and the low false-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 8 publications
1
22
1
Order By: Relevance
“…However, amounts of CMV DNA due to contamination with genital secretions or mother´s milk after breastfeeding should be smaller than CMV DNA levels resulting from cCMV infection. Consistently, participants with false positive saliva screening samples had significantly lower viral load levels than participants with confirmed congenital CMV infection (see above, [1,21,31]. The percentage of false positive screening results also differed largely between the studies varying from 7.5% to 41% of samples positive in the initial screen.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, amounts of CMV DNA due to contamination with genital secretions or mother´s milk after breastfeeding should be smaller than CMV DNA levels resulting from cCMV infection. Consistently, participants with false positive saliva screening samples had significantly lower viral load levels than participants with confirmed congenital CMV infection (see above, [1,21,31]. The percentage of false positive screening results also differed largely between the studies varying from 7.5% to 41% of samples positive in the initial screen.…”
Section: Discussionmentioning
confidence: 71%
“…Contamination of neonatal saliva samples by CMV DNA present in genital secretions in the birth canal during delivery [10] or in the milk remaining from the last breast feeding [11,30] are possible reasons for that. Ross et al concluded that breastfeeding in the first weeks of life contributes to low but acceptable rates (0.03-0.14%) of false positive saliva PCR results [31]. However, amounts of CMV DNA due to contamination with genital secretions or mother´s milk after breastfeeding should be smaller than CMV DNA levels resulting from cCMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about false positive results with these samples have been raised because virus transmission during breastfeeding may occur. Several articles reported the excretion of this virus in the breast milk of healthy women [ 22 , 23 ]. To prevent these false-positive during screening programs an approach would be to instruct health professionals to collect the sample before the first breastfeeding, although this is not always possible.…”
Section: Discussionmentioning
confidence: 99%
“…The use of saliva samples for detection of congenital CMV infection has been shown to be very sensitive (>97%) and specific (99%) in a prospective multicenter study (Boppana et al, 2011). Although CMV shedding in mothers' breastmilk could lead to falsepositive results when using saliva for detection of congenital infection, the false-positive rates has been shown to be very low, which ranged from 0.03% to 0.14% (Ross et al, 2018). In our study, the median time of saliva sample collection of the CMV-positive was 0 days (0À14 days) after birth.…”
Section: Discussionmentioning
confidence: 99%